Mencari Kepastian Hukum dalam Sistem Peradilan Pidana Pemilu - Sonang Mauludin Malik (Jurnal Hukum Lex Generalis, 2026)
This research discusses the handling of electoral offenses, specifically those committed by election administrators. The purpose of this study is to describe the various forms of electoral offenses that occur during elections and to explain their law enforcement mechanisms. Law enforcement in electoral offenses must be executed strictly so that electoral law enforcement can be implemented effectively as an instrument to realize integral, honest, and fair elections. The method used in this study is normative legal research (normative-juridical), utilizing primary, secondary, and tertiary legal sources. The results indicate that there are election administrators proven to have committed electoral offenses but who cannot be prosecuted because the legal process exceeded the statutory resolution deadline. Specifically, the regulation requires the resolution of electoral offenses to be completed no later than 5 (five) days before the General Elections Commission (KPU) certifies the election results nationally. This condition compromises the public's sense of justice, as perpetrators proven to have committed a crime escape punishment due to procedural non-compliance (failure to meet formal requirements). Therefore, legal reform is urgently needed to achieve legal certainty within the electoral criminal justice system.